La grafomotricidad en el desarrollo de la lectoescritura en el nivel de preparatoria - Chicaiza Chicaiza, Tatiana Vanessa (2023)
The present research was carried out with the purpose of determining graphomotor skills in the development of reading and writing at the high school level, the work had the objective of diagnosing the development of reading and writing through graphomotor skills in high school children of the "Belisario Quevedo" Educational Unit, in this sense, the level of reading and writing and their graphomotor control of high school students was observed, with this it is possible to see the factors that are affecting and what can be done to improve their learning. It is based on a qualitative approach, with a non-experimental research design, bibliographic type of research. The interview technique was applied, observation with its corresponding instruments, the guide of questions, observation sheet. For this reason, this process was developed by carrying out practical activities with each of the students, taking into account each indicator of the observation sheet, in which one of the most important was the handling of the digital tweezers, since based on the indicator named, the execution of the rest of the activities could be evidenced, therefore, the diagnosis was validated by experts and users, who through their knowledge and work experience showed how to improve or implement strategies that benefit their progress in reading and writing. Thus, it is concluded that the application of graphomotor skills is important, through its methodology, to help educate children from early childhood, allowing them to acquire significant learning.